T2 relaxation time of the normal-appearing white matter is related to the cognitive status in cerebral small vessel disease. Issue 7 (July 2021) - Brandhofe, Annemarie; Stratmann, Christoph; Schüre, Jan-Rüdiger; Pilatus, Ulrich; Hattingen, Elke; Deichmann, Ralf; Nöth, Ulrike; Wagner, Marlies; Gracien, René-Maxime; Seiler, Alexander
Previous diffusion tensor imaging (DTI) studies indicate that impaired microstructural integrity of the normal-appearing white matter (NAWM) is related to cognitive impairment in cerebral small vessel disease (SVD). This study aimed to investigate whether quantitative T2 relaxometry is a suitable imaging biomarker for the assessment of tissue changes related to cognitive abnormalities in patients with SVD. 39 patients and 18 age-matched healthy control subjects underwent 3 T magnetic resonance imaging (MRI) with T2-weighted multiple spin echo sequences for T2 relaxometry and DTI sequences, as well as comprehensive cognitive assessment. Averaged quantitative T2, fractional anisotropy (FA) and mean diffusivity (MD) were determined in the NAWM and related to cognitive parameters controlling for age, normalized brain volume, white matter hyperintensity volume and other conventional SVD markers. In SVD patients, quantitative T2 values were significantly increased compared to controls (p = 0.002) and significantly negatively correlated with the global cognitive performance (r= –0.410, p = 0.014) and executive function (r= –0.399, p = 0.016). DTI parameters did not correlate with cognitive function. T2 relaxometry of the NAWM seems to be sensitive to microstructural tissue damage associated with cognitive impairment in SVD and might be a promising imaging biomarker for evaluation of disease progression and possible effects of therapeutic interventions.